PENGARUH CURRENT RATIO, DEBT TO EQUITY RATIO, DAN TOTAL ASSET TURNOVER TERHADAP RETURN ON ASSET PADA PERUSAHAAN PERBANKAN DI BEI 219-2023 - Fitriyana M. Rukin; Rudi Kurniawan; Dian Prawitasari; Ida Farida (LPPM Politeknik Pratama, 2025)
This study investigates the effect of Current Ratio (CR), Debt to Equity Ratio (DER), and Total Asset Turnover (TATO) on Return on Assets (ROA) in banking companies listed on the Indonesia Stock Exchange (IDX) during 2019–2023. Using purposive sampling, 20 companies were selected over 5 years (100 observations). Multiple linear regression analysis shows that CR has a significant positive effect on ROA, DER has no significant effect, while TATO has a significant negative effect on ROA.